Dissolution of the Eudialyte-Group Minerals: Experimental Modeling of Natural Processes - Julia A. Mikhailova; Yakov A. Pakhomovsky; Galina O. Kalashnikova; Sergey M. Aksenov (Minerals, 2022)
Eudialyte-group minerals (EGMs) are typical accessory or rock-forming minerals of the Lovozero peralkaline massif (Kola Peninsula, Russia). The EGM grains in the rocks of the massif are often replaced by an association of various secondary minerals such as lovozerite and wöhlerite group minerals, as well as terskite, catapleiite, elpidite, gaidonnayite, vlasovite, zircon, and loparite-(Ce). However, EGMs in the Lovozero massif can be not only pseudomorphized, but also partially or completely dissolved. The partial dissolution of eudialyte grains was simulated in three series of experiments, and the results obtained were compared with natural samples. Observations in natural samples and experimental studies have shown that the partial dissolution of eudialyte-group minerals occurs in two stages: (1) loss of sodium and hydration; (2) loss of other cations not included in the zirconosilicate framework. This process proceeds most intensively in acidic hydrothermal solutions and may be responsible for the appearance of new mineral species in the eudialyte group.